INVESTIGATION THE DEEP AND SURFACE LEARNING APPROACHES OF ACCOUNTING STUDENTS IN TERMS OF VARIOUS VARIABLES - ÖZTÜRK, Meryem (Business & Management Studies: An International Journal, 2018)
The purpose of the study is to determine whether there is a relationship between the learning approaches of the accounting students and demographic variables, the attendance to accounting courses and the daily repetition of accounting courses. In the scope of the study, a questionnaire was applied to Atatürk University Erzurum Vocational School Accountancy and Tax Applications Program students. According to the results of study, it was determined that there was a statistically significant relationship between the students’ deep learning approach and daily repetition of accounting subject, the high school type they graduate and classroom level; it was determined that there was a statistically significant relationship between the students’ surface learning tendency and gender, university preference order, attendance to accounting courses and daily repetition of accounting courses. When compared to the first-year students second-year students have higher deep learning tendencies and when compared to the other students, the students who graduated from the Open Education High School have higher than deep learning tendencies. The surface learning tendencies of the students who prefer the program in the first order is higher than those who prefer the program in the next order and the surface learning tendencies of man students is higher than female students. In addition, while deep learning tendency of students who daily repetition of accounting courses have a higher degree than other students, surface learning tendencies are lower.